The racketeer - Grisham, John (Doubleday, 2012)
Given the importance of what they do, and the controversies that often surround them, and the violent people they sometimes confront, it is remarkable that in the history of this country only four active federal judges have been murdered. Judge Raymond Fogletree just became number five. His body was found in the basement of a lakeside cabin he had built himself and frequently used on weekends. When he did not show up for a trial on Monday morning, his law clerks panicked, called the FBI, and in due course the agents found the crime scene. There was no forced entry, no struggle, just two dead bodies--Judge Fogletree and his young secretary. I did not know Judge Fogletree, but I know who killed him, and why. I am a lawyer, and I am in prison. It's a long story. --publisher.